Robust Regression with Continuous and Categorical Variables Having Heteroscedastic Non-Normal Errors - Majeed Al-Talib, Bashar Abdul Aziz (2006)
The performance of the classical Ordinary Least Squares (OLS) method can be very poor when the data set for which one often makes a normal assumption, has a heavy- tailed distribution which may arise as a result of outliers. The problem is further complicated when the variances of the error terms are not constant.